Efekty koncentracji uspołecznionych przedsiębiorstw handlu miejskiego w Polsce - Michalak, Adolf (Wydział Prawa i Administracji UAM, 1978)
The author presents in the article various — positive and negative — effects of a concentration of the state and co-operative urban trade enterprises in Poland. Then he proposes some solutions increasing positive effects of the concentration. The notion „concentration" means the process of increasing the average size of the enterprises during a certain period of time. This process includes: 1) expansion of some existing enterprises, while the number of others decreases (or without any decrease), 2) emergence of new, bigger enterprises, 3) mergence of enterprises. To increase the positive effects of the concentration the author proposes to intensify the process of functional integration of the trade enterprises located on the same territory. Despite recently carried out concentration the trade enterprises are too small to specialize in particular commercial functions.
Effects of the Concentration of the Socialized Urban Trade Enterprises in Poland